Engineer on a green mission Dane goes to great lengths to promote conservation EXPAT @HOME - The star, Yip Yoke Teng (2012)
DENMARK-born energy engineer Gregers Reimann is one expatriate who does not mind taking pains to make Kuala Lumpur greener.